Reversed-Phase UHPLC Enantiomeric Separation of Rasagiline Salts Using a Chiralpak® AGP Column - Nagarajan Balaji; Sayeeda Sultana (MDPI AG, 2017)
We report the first rapid ultra-high performance liquid chromatographic (UHPLC) enantiomeric reversed-phase separation of rasagiline mesylate and its tartrate salts using a Chiralpak® AGP column (50 mm × 2.1 mm, 5 μm) as a stationary phase. This method was developed as an alternative to the usage of previously reported normal-phase chiral LC columns for isomer separation. Our method is based on an isocratic approach using a mixture of ammonium acetate and isopropyl alcohol (90:10, v/v) as the mobile phase (0.6 mL/min flow rate). The detection limit (at a detection wavelength of 210 nm) and quantification limit for the rasagiline enantiomers were 0.06 and 0.2 μg/mL, respectively. This method is compatible with the UHPLC-MS technique. The successful separation of rasagiline and its enantiomer was confirmed by determining the corresponding specific optical rotation values. Our method will be applicable for detecting rasagiline enantiomers during the control of manufacturing processes, and for use in rapid analysis for quality control in pharmaceutical industry to obtain optically pure pharmaceutical substances. This method was validated in terms of its precision, limit of detection, limit of quantification, linearity, accuracy, robustness, ruggedness, specificity, forced degradation, and solution stability, according to International Council on Harmonization Validation Guidelines Q2 (R1).